PROSES ADAPTASI MIGRAN SIRKULER : KASUS MIGRAN ASAL KOMUNITAS PERKEBUNAN THE RAKYAT CIANJUR, JAWA BARAT - HERLINA TARIGAN (SOCA: Jurnal Sosial Ekonomi Pertanian, 2004)
Circular migrant adaptation process: Case of migrants originated from TeaSmallholder Plantation Community in Cianjur, West Java. Value of work orientationchanges from agriculture towards non-agriculture has caused higher populationmobility from rural to urban areas. Sociologically, this geographical or spatial mobilityis also a socio-cultural mobility from traditional agriculture towards modern industry.Migrants should be adaptive to new situation so that the purpose of migrating wouldbe achieved. The objectives of the study are to investigate: (1) influencing factors ofpopulation migration; (2) Adaptation process of migrants originated from smallholderplantation community in Cianjur working in Tangerang Industrial Areas. The studyapplied qualitative method with case study strategy. The results of the study showedthat economic and social factors pushed the migration cases complimentarily.Adaptation process by maintaining “in group feeling” succeeded in providing sense ofserenity and comfort ability although it seemed to get acculturation process sloweddown. Orientation of working for the future directed the migrants to keep makingrelation with their relatives or their hometown communities